Tinjauan Campuran Beton Normal dengan Penggunaan Superplasticizer Sebagai Bahan Pengganti Air Sebesar 0%; 0,3%; 0;5% Dan 0,7% Berdasarkan Berat Semen - Abdullah Faqihuddin; Hermansyah Hermansyah; Eti Kurniati (Program Studi Sarjana Teknik Sipil Universitas Internasional Batam, 2021)
The use of Superplasticizer as a substitute for water in the concrete mixture can increase fatigue with a level of workability that is easy to work, reduce the amount of water up to 20% and increase the compressive strength value higher than normal concrete. PPC cement contains a pozzolanic substance with a particle size smaller than cement which is able to fill the smallest cavities in the concrete mixture to obtain high tightness and density. The purpose of this study was to determine the ratio of the increase between compressive strength and workability in normal concrete mixtures with the use of superplasticizer as a substitute for water and PPC cement. Calculation procedure for normal concrete mix design based on SNI 03-2843-2000, variation of superplasticizer used to replace water is 0.3%; 0.5% & 0.7% based on the weight of cement, the value of the cement water factor (FAS) is 0.42 and the compressive strength value is 25 MPa. The compressive strength test was carried out at the age of 7 days and 28 days. The results of this study indicate that the use of variations superplasticizer as a substitute for water affects thevalue slump, volume weight and compressive strength value of concrete. Thevalue slump highestat a variation of 0.5% is 17 cm, included in thevalue slump plan. Heavy volume 0.7% maximum variation of 2402.4 kg / m3,entered the category of normal berbebot concrete. The highest compressive strength value at 7 days at a variation of 0.5% was 37.5 MPa with a percentage increase in compressive strength obtained at 17.77%, the compressive strength value reached the compressive strength of the plan. The highest compressive strength value at 28 days at a variation of 0.7% is 43.4 MPa with a percentage increase in compressive strength of 17.81%, the compressive strength value at 28 days is included in the high quality concrete category